How Much Should an Investor Trust the Startup Entrepreneur? - A Network Model - Anna Klabunde (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
Trust is an important determinant of start-up financing. In a simple agentbased model it is determined what the best trusting strategy is for a collective of investors and whether it is rational for an individual investor to deviate from this collective optimum. Trust depends on a measure of social distance and is the precondition for investment. Trust increases and decreases based on whether an investor is satisfied with the interest payments received from an entrepreneur. If an investor is dissatisfied, he terminates the relation with the entrepreneur. For assessing the quality of their own investments, investors communicate with other investors in a network-like structure. I find that, as a collective, it is best for investors to compare their returns critically in order to identify unproductive entrepreneurs, but to be tolerant regarding existing links to entrepreneurs in order not to terminate profitable relations because of minor productivity drops. However, it is optimal for an individual investor to deviate from this strategy and to be less easily disappointed, but to decrease trust in larger steps. In a sense, an individual investor can freeride on the others' critical assessment. If all investors behave according to this latter strategy, too many unproductive firms remain in the market and the average investor's return is lower than in the collective optimum. – – Vertrauen ist ein wichtiger Faktor in der Startup-Finanzierung. In einem einfachen agentenbasierten Modell wird untersucht, welches die beste Vertrauensstrategie für eine Gruppe von Investoren ist, und ob es einen einzelnen Investoren besser stellt, wenn er von diesem kollektiven Optimum abweicht. Anfängliches Vertrauen hängt von sozialer Entfernung ab und ist die Voraussetzung für Investitionen. Vertrauen wächst und schrumpft je nachdem, ob ein Investor mit dem Return, den eher von einem Unternehmer erhält, zufrieden ist. Wenn ein Investor unzufrieden ist, beendet er die Investitionsbeziehung. Um die Höhe ihres eigenen Returns einschätzen zu können, kommunizieren Investoren in einer netzwerkartigen Struktur miteinander. Ich zeige, dass es für Investoren als Kollektiv am besten ist, Returns kritisch zu vergleichen um unproduktive Unternehmer zu identifizieren, dann aber Vertrauen nur in kleinen Schritten zu verlieren, um profitable Beziehung nicht wegen geringfügiger negativer Produktivitätsschocks zu beenden. Ein einzelner Investor kann sich jedoch besser stellen, indem er von dieser Strategie abweicht und weniger leicht enttäuscht ist, dafür aber Vertrauen bei Enttäuschung schnell verliert. Gewissermaßen können individuelle Investoren die kritische Bewertung durch die anderen ausnutzen, weil sichergestellt ist, dass unproduktive Unternehmer ohnehin nicht bestehen. Wenn sich allerdings alle Investoren so verhalten, verbleiben zu viele unproduktive Unternehmer im Markt und der durchschnittliche Return der Investoren ist geringer als im kollektiven Optimum.
Keywords: C63; G02; G24; L26; 330; business angel investment; trust; entrepreneurship; agent-based simulation